2017
DOI: 10.1093/ageing/afx122
|View full text |Cite
|
Sign up to set email alerts
|

Shared genetic influence on frailty and chronic widespread pain: a study from TwinsUK

Abstract: Introductionfrailty is an increased vulnerability to adverse health outcomes, across multiple physiological systems, with both environmental and genetic drivers. The two most commonly used measures are Rockwood’s frailty index (FI) and Fried’s frailty phenotype (FP).Material and methodsthe present study included 3626 individuals from the TwinsUK Adult Twin Registry. We used the classical twin model to determine whether FI and FP share the same latent aetiological factors. We also investigated the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 26 publications
3
30
2
Order By: Relevance
“…Our SNP-based heritability estimate of 14% for the FI was slightly lower than previous family-or twin-based estimates between 19 and 45% (Livshits, Lochlainn, et al 2018) (Murabito et al 2012) (Young et al 2016). This is expected as this SNP-based estimate does not include rare, structural, non-additive, or non-autosomal genetic influences.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Our SNP-based heritability estimate of 14% for the FI was slightly lower than previous family-or twin-based estimates between 19 and 45% (Livshits, Lochlainn, et al 2018) (Murabito et al 2012) (Young et al 2016). This is expected as this SNP-based estimate does not include rare, structural, non-additive, or non-autosomal genetic influences.…”
Section: Discussioncontrasting
confidence: 94%
“…The mechanisms underlying frailty are likely multifactorial but not well understood. Studies have suggested a genetic basis, with heritability estimates between 19 and 45% (Livshits, Lochlainn, et al 2018) (Murabito et al 2012) (Young et al 2016). Candidate gene association studies for frailty have suggested the involvement of genes in inflammatory pathways (Viña et al 2016), including tumour necrosis factor (Mekli et al 2016) and interleukin-18 (Mekli et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Another area for exploration is whether genetic susceptibility to physical frailty is associated with differences in cognitive ageing. Twin studies have reported heritability estimates for physical frailty of around 40%,30 31 however, in the small cohorts studied to date, no genetic variant has been consistently associated with this phenotype. Meta-analysis of genome-wide association studies of physical frailty should throw light on which genetic variants confer susceptibility, allowing the construction of polygenic risk scores.…”
Section: Discussionmentioning
confidence: 99%
“…The biological mechanisms underlying frailty have been extensively studied in recent years. 15 , 26 We have shown that interindividual variation of frailty scores significantly depends on genetic factors, which explain 34% of their variation. We also found that chronic widespread musculoskeletal pain (CWP)—another prevalent age-related condition—is significantly associated with the Rockwood Frailty Index (FI), and that this association is caused by shared genetic and common environmental factors.…”
Section: Introductionmentioning
confidence: 99%